Intraoperative Hemodynamic Fluid Therapy for Immediate- to High-risk Non-cardiac Surgery: A Narrative Review - Petsakul, Suttasinee; Prathep, Sumidtra; Tanasansuttiporn, Jutarat; Akaraborworn, Osaree (Journal of Health Science and Medical Research, 2023)
The rates of perioperative morbidity and mortality during major surgery have shown a declining trend due to improvements in hemodynamic monitoring and fluid assessment. However, several million surgical procedures involving aged patients and those with multiple comorbidities are performed every year worldwide. Thus, the establishment and constant re-evaluation of appropriate threshold values of perioperative hemodynamic parameters for the management of immediate- to high-risk patients with a narrow safety margin are especially important. Perioperative fluid balance is an important independent risk factor of postoperative morbidity and mortality. In this article, we provide an overview of intraoperative hemodynamic fluid resuscitation and fluid-response monitoring during non-cardiac surgery. We also focus on targets at the macrocirculatory, microcirculatory, and cellular levels.